A critical discourse analysis of Zimbabwe’s Transitional Stabilisation Programme (TSP) with specific reference to potential implementation dynamics - Chapanga, Evans (University of the Free State, 2020)
This study is premised on the argument that there is a gap between policy formulation and implementation which can be explained in linguistic terms. A case study research of Zimbabwe’s Transitional Stabilisation Programme (TSP) economic policy has been used to examine the direct connection between the critical processes of policy formulation and implementation. As the ‘turbulent flow’ model of public policy making processes reveals, it is possible to establish direct connections between the processes traditionally viewed as linear and fragmented stages. Through deployment of Critical Discourse Analysis (CDA) specifically Norman Fairclough’s Three Dimensional Model of discourse analysis, overt and covert discourses with grave implications for policy implementation are decipherable. The tenet of CDA provides for interdependent levels of analysis which are textual analysis, discursive and socio-cultural practices. The three pronged attack on the policy text describes, interprets and explains discourses bringing to the fore intratextual, intertextual and ideological issues which fortify the linguistic variable in explaining the gap between policy and implementation. A critical analysis of linguistic features inside and outside the official state text suggests disconnect between policy formulation and implementation. At text analysis level there are examples of linguistic features used which lack conviction, forthrightness and in some instances make stringent conditions which complicate implementation processes. At this level of analysis it is prudent to highlight that the study is not mere pursuit of faults or deficits in the policy document as this translates to a witch hunt exercise. Instead there is positive framing of discourses within the text structure theme which on the surface provides for orderliness but on close analysis there are issues of complexity and density which complicate implementation processes. Similarly optimistic discourses appearing on the surface as positive in reality though place the end users of the policy in an invidious in which they are expected to deliver regardless of prevailing circumstances and objective realties. Socio-economic and political discourses playing out in the public domain indicate that interpretation poses a challenge in the appreciation, conceptualisation and comprehension of the policy initiatives and provisions. Interpretation challenges which cut across the levels are more pronounced at the second level of analysis within the frame of Intertextuality, production and distribution. At the third level of analysis, there is the ideological construct which revolves in the main around purported nation building under the auspices of the ‘new government’. There are issues connected to policy formulation which have grave implications for social cohesion and subsequent buy-in of the policy initiatives, interventions and provisions. For instance, unity which is a critical pillar in the promotion, cultivation and sustenance of social cohesion is blighted by diatribe against the Old Dispensation structures. Therefore, the interrelated levels of analysis trigger overt and covert discourses potentially serving as a gap between policy formulation and implementation. Although exogenous factors such as social, economic and political variables are critical in explaining the gap between a policy and its implementation the centrality of the linguistic variable is attributable to the reality that it is the vehicle that transmits and couches the other variables. Complex thinking around the linguistic variable involves combining the apparent and latent discourses to ascertain predisposition of the policy to implementability. What motivates policy makers to formulate policies with potential seeds of failure remains speculative thus warranting further research so that the puzzle in policy making processes is unraveled.
Thesis (Ph.D. (Linguistics and Language Practice))--University of the Free State, 2020
Keywords: Zimbabwe’s Transitional Stabilisation Programme (TSP) -- Economic policy